(untitled) (Cultura Económica, 2019)
This paper presents a critical study of Amartya Sen’s book, The Idea of Justice. First, the contrasts between pragmatism and objectivity in the idea of justice proposed by Sen are analyzed. Then, the concept of ‘capability’ proposed by this economist is developed, and Martha Nussbaum’s objections to this approach are presented. Further, the article explores the links between the idea of justice and Amartya Sen’s economic conceptions, and analyzes the discussion about the maximizing diagram carried out by this thinker and Elizabeth Anderson. Finally, an assessment of the work as a whole is made, highlighting the importance of practical reason in the analysis of justice.